(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
This article philosophically analyzes the role of the malomatism (reproof) ideas which arose on the basis of the tariqa of tasawwuf (Sufism), in the development of Islamic Sufism. The cultural development of various tariqas and teachings in interconnection is scientifically substantiated.